Yellowing-resistant flame-retardant plastic and preparation method thereof

By using silicon, tungsten, and yttrium plasma currents in polypropylene particles to form an amorphous silicon thin film and conductive network, the electrostatic problem of polypropylene materials during processing is solved, and the mechanical strength and anti-static properties of the material are improved.

CN119505299APending Publication Date: 2025-02-25王剑涛
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411423848.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The existing polypropylene materials are prone to static electricity during processing, and the antistatic agent has poor heat resistance and easy decomposition during processing, which has poor compatibility with the matrix resin, resulting in a decline in the mechanical properties of the material.

Method used

By introducing silicon, tungsten, yttrium plasma currents into the polypropylene particles, an amorphous silicon thin film and conductive network are formed to enhance the mechanical strength and anti-static properties of the material.

Benefits of technology

Significantly improve the surface hardness and overall mechanical strength of polypropylene, enhance antistatic and antibacterial properties, and improve the wear resistance and flexibility of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005081601770000071
    Figure BDA0005081601770000071
Patent Text Reader

Abstract

The invention discloses a yellowing-resistant flame-retardant plastic and a preparation method thereof, and relates to the technical field of polypropylene particle preparation. Potassium ethylene trifluoroborate and allyl hydrazine hydrochloride participate in propylene polymerization to prepare modified polypropylene, fluorine and boron elements are introduced, growth and reproduction of bacteria are inhibited, the antibacterial effect is achieved, meanwhile, potassium ions adsorb moisture in air, the antistatic effect is achieved, chloride ions are assisted, and the antibacterial performance is enhanced; then, the modified polypropylene particles are bombarded through silicon, tungsten and yttrium mixed plasma current, an amorphous silicon film is formed on the surface through in-situ growth, and the surface hardness and the overall mechanical strength of polypropylene are remarkably improved; by doping the tungsten element, the friction coefficient is reduced, the wear is reduced, the wear resistance and the mechanical property of the plastic are improved, the yttrium element is matched, grains are refined, the mechanical strength and the flexibility of the material are improved, and on the basis, the tungsten element and the yttrium element form a conductive network on the surface, so that generated electrostatic charges are quickly leaked, and the antistatic effect is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polypropylene particle preparation, in particular to yellowing-resistant flame-retardant plastic and a preparation method thereof. Background Art

[0002] Plastic products are widely used in modern people's daily life, including kitchen appliances, food packaging, medical products and children's products. These plastic products are made of organic polymers. At the same time, some organic additives need to be added during the production process to facilitate product processing or meet certain performance requirements. These organic substances make it easy for bacteria to grow on the surface of plastics, which is harmful to the health of users. Therefore, antibacterial plastics have become a very important type of functional plastics.

[0003] Moreover, as the application of polymer materials becomes more and more extensive, its disadvantages become more and more obvious, and static electricity is one of them. In order to eliminate static electricity on the surface of materials, various antistatic agents are added to polymer materials. However, while antistatic agents eliminate static electricity on the surface of materials, they also bring many other problems. For example, antistatic agents have poor heat resistance, are easy to decompose during processing, have poor compatibility with matrix resins, destroy the original structure of polymer materials, and reduce the mechanical properties of materials. Therefore, it is particularly important to invent a kind of antistatic, antibacterial, high-strength modified polypropylene particles. Summary of the invention

[0004] The object of the present invention is to provide a yellowing-resistant flame-retardant plastic and a preparation method thereof, so as to solve the problems existing in the prior art.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: a yellowing-resistant flame-retardant plastic and a preparation method thereof, comprising the following preparation steps:

[0006] (1) Under nitrogen protection, 11-23 parts of potassium ethylene trifluoroborate, 5-17 parts of allylhydrazine hydrochloride, 74-132 parts of toluene, and 46-78 parts of acetonitrile are mixed uniformly, the rotation speed is adjusted to 140 rpm, 2-4 parts of catalyst are added, propylene gas is introduced to a certain pressure, the temperature is raised to 60-70° C., and the reaction is carried out for 4-8 hours. During the reaction, propylene gas is continuously introduced to keep the pressure constant. After the reaction is completed, the air is connected, 15-29 parts of hydrochloric acid ethanol solution are added, and the mixture is stirred for 40-60 minutes. The solid is filtered out, washed with deionized water for 3 times, and dried at 70-90° C. for 6-10 hours to obtain modified polypropylene;

[0007] (2) adding 85 to 119 parts of modified polypropylene, 3 to 7 parts of lubricant, 5 to 11 parts of antioxidant, and 1 to 5 parts of benzotriazole light stabilizer into a mixer and mixing for 30 to 40 minutes, putting into a mixing extruder for extrusion, and pelletizing to obtain modified polypropylene pellets;

[0008] (3) Place the modified polypropylene particles in a vacuum of 5.0x10 -3 Pa environment, then, filled with argon, and cleaned in sequence at 300V bias voltage and 900V ion beam voltage, each time for 10 minutes, introduced mixed plasma by magnetron sputtering silicon target, tungsten target and yttrium target, and controlled silicon, tungsten and yttrium plasma currents, under the conditions of argon flow rate of 45sccm and bias voltage of -60V, deposited for 4 to 6 hours to obtain antistatic and antibacterial modified polypropylene particles.

[0009] Furthermore, the certain pressure in step (1) is 5 MPa.

[0010] Furthermore, the catalyst in step (1) is any one of a Ziegler-Natta catalyst, a Phillips catalyst, and a Metallocene catalyst.

[0011] Furthermore, the concentration of hydrochloric acid in the hydrochloric acid ethanol solution in step (1) is 3 mol / L.

[0012] Furthermore, the lubricant in step (2) is any one of stearic acid acetamide, distearylamide, and oxidized polyethylene wax.

[0013] Furthermore, the antioxidant in step (2) is any one of butylated hydroxytoluene, antioxidant 1010, and antioxidant 1076.

[0014] Furthermore, the temperature of the mixer in step (2) is 160-180°C.

[0015] Furthermore, the parameters of the mixing extruder in step (2) are: head temperature 155-185°C, screw speed 200-230r / min, extrusion pressure 10-12MPa, shear rate 220-240s -1 .

[0016] Furthermore, in step (3), the flow rate of the argon gas is 40 sccm.

[0017] Furthermore, in step (3), the silicon, tungsten and yttrium plasma currents are 2.5A, 0.3A and 0.4A respectively.

[0018] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0019] The invention uses silicon, tungsten and yttrium mixed plasma current bombardment to modify CC bonds and CH bonds in polypropylene particles to form active chains, which are combined with the mixed plasma. At the same time, the active chains react with each other to form a stable cross-linking structure, which blocks the active chains from continuing to overflow, and then grows in situ on the surface of polypropylene to form an amorphous silicon film, which significantly improves the surface hardness and overall mechanical strength of the polypropylene, and at the same time improves the flame retardant performance of the plastic. The doping of tungsten elements can reduce the friction coefficient of the amorphous silicon film, reduce wear when friction occurs, and then improve the wear resistance of the plastic and enhance the mechanical performance. The yttrium element is combined to fill the defects of the polypropylene and the film grains, so that the grains are refined, the grain boundary area is increased, and the barrier effect of the grain boundary on the dislocation is enhanced, so that the dislocation density of the material is reduced, and the mechanical strength and flexibility of the material are improved. On this basis, the tungsten and yttrium elements have good electrical conductivity, and form a conductive network on the surface, so that the generated static charge is quickly leaked, and the antistatic effect is achieved.

[0020] Among them, modified polypropylene is prepared by the polymerization of propylene with potassium trifluoroborate of ethylene and allylhydrazine hydrochloride; the introduction of fluorine and boron elements through potassium trifluoroborate of ethylene can penetrate the bacterial cell membrane, destroy the bacterial metabolic process, inhibit the growth and reproduction of bacteria, and achieve antibacterial effect. At the same time, the presence of potassium ions can increase its conductivity and hygroscopicity by absorbing water molecules in the air, thereby achieving antistatic effect, assisting the chloride ions in allylhydrazine hydrochloride to further enhance the antibacterial properties. On this basis, the hydrazide structure has a higher reactivity, and cooperates with the plasma current to make the amorphous silicon film more tightly bonded, thereby further enhancing the mechanical strength. DETAILED DESCRIPTION

[0021] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0022] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the various index testing methods of the antistatic and antibacterial modified polypropylene particles prepared in the following examples are as follows:

[0023] Tensile strength: The plastic particles of the embodiment and the comparative example were made into 0.3 mm films for tensile strength test, and the test was performed in accordance with GB / T 13022.

[0024] Abrasion test: Take the same weight of the embodiment and the comparative example, and test the wear resistance of the plastics according to GB / T 3960, and record the wear quality.

[0025] Surface resistance: The same weight of the embodiment and the comparative example was used to make a square plate of 100 mm×100 mm×3 mm, and the test was performed according to GB / T 1410.

[0026] Antibacterial rate: Take the examples and comparative examples of the same mass and test them according to QB / T 2591.

[0027] Example 1

[0028] (1) Under nitrogen protection, 11 parts of potassium ethylene trifluoroborate, 5 parts of allylhydrazine hydrochloride, 74 parts of toluene, and 46 parts of acetonitrile were mixed uniformly, the rotation speed was adjusted to 140 rpm, 2 parts of Ziegler-Natta catalyst were added, propylene gas was introduced to 5 MPa, the temperature was raised to 60° C., and the reaction was carried out for 4 hours. During the reaction, propylene gas was continuously introduced to keep the pressure constant. After the reaction was completed, the air was connected, 15 parts of 3 mol / L hydrochloric acid ethanol solution was added, and the mixture was stirred for 40 minutes. The solid was filtered out, washed with deionized water 3 times, and dried at 70° C. for 6 hours to obtain modified polypropylene;

[0029] (2) 85 parts of modified polypropylene, 3 parts of stearic acid acetamide, 5 parts of butylated hydroxytoluene, and 1 part of phenyltriazole light stabilizer were added to a mixer and mixed at 160°C for 30 minutes, and then put into a mixing extruder for extrusion. The parameters were as follows: head temperature of 155°C, screw speed of 200 r / min, extrusion pressure of 10 MPa, and shear rate of 220 s -1 , pelletizing to obtain modified polypropylene particles;

[0030] (3) Place the modified polypropylene particles in a vacuum of 5.0x10 -3 Pa environment, then, argon gas was filled at a flow rate of 40sccm, and cleaning was carried out in sequence at a bias voltage of 300V and an ion beam voltage of 900V, each time for 10min, and mixed plasma was introduced by magnetron sputtering silicon target, tungsten target and yttrium target, and the plasma currents of silicon, tungsten and yttrium were controlled to 2.5A, 0.3A and 0.4A, respectively. Under the conditions of argon flow rate of 45sccm and bias voltage of -60V, deposition was carried out for 4h to obtain antistatic and antibacterial modified polypropylene particles.

[0031] Example 2

[0032] (1) Under nitrogen protection, 17 parts of potassium ethylene trifluoroborate, 11 parts of allylhydrazine hydrochloride, 103 parts of toluene and 62 parts of acetonitrile were mixed evenly, the rotation speed was adjusted to 140 rpm, 3 parts of Phillips catalyst were added, propylene gas was introduced to 5 MPa, the temperature was raised to 65° C., and the reaction was carried out for 6 hours. During the reaction, propylene gas was continuously introduced to keep the pressure constant. After the reaction was completed, the air was connected, 22 parts of 3 mol / L hydrochloric acid ethanol solution was added, and the mixture was stirred for 50 minutes. The solid was filtered out, washed with deionized water for 3 times, and dried at 80° C. for 8 hours to obtain modified polypropylene;

[0033] (2) 102 parts of modified polypropylene, 5 parts of distearamide, 8 parts of antioxidant 1010, and 3 parts of benzotriazole light stabilizer were added to a mixer and mixed at 170°C for 35 minutes, and then put into a mixing extruder for extrusion. The parameters were as follows: head temperature of 170°C, screw speed of 215 r / min, extrusion pressure of 11 MPa, and shear rate of 230 s -1 , pelletizing to obtain modified polypropylene particles;

[0034] (3) Place the modified polypropylene particles in a vacuum of 5.0x10 -3 Pa environment, then, argon gas was filled at a flow rate of 40sccm, and cleaning was carried out in sequence at a bias voltage of 300V and an ion beam voltage of 900V, each time for 10min, and mixed plasma was introduced by magnetron sputtering silicon target, tungsten target and yttrium target, and the plasma currents of silicon, tungsten and yttrium were controlled to 2.5A, 0.3A and 0.4A, respectively. Under the conditions of argon flow rate of 45sccm and bias voltage of -60V, deposition was carried out for 4 to 6h to obtain antistatic and antibacterial modified polypropylene particles.

[0035] Example 3

[0036] (1) Under nitrogen protection, 23 parts of potassium ethylene trifluoroborate, 17 parts of allylhydrazine hydrochloride, 132 parts of toluene, and 78 parts of acetonitrile were mixed uniformly, the rotation speed was adjusted to 140 rpm, 4 parts of Metallocene catalyst were added, propylene gas was introduced to 5 MPa, the temperature was raised to 70° C., and the reaction was carried out for 8 hours. During the reaction, propylene gas was continuously introduced to keep the pressure constant. After the reaction was completed, the air was connected, 29 parts of 3 mol / L hydrochloric acid ethanol solution was added, and the mixture was stirred for 60 minutes. The solid was filtered out, washed with deionized water for 3 times, and dried at 790° C. for 10 hours to obtain modified polypropylene;

[0037] (2) 119 parts of modified polypropylene, 7 parts of oxidized polyethylene wax, 11 parts of antioxidant 1076, and 5 parts of benzotriazole light stabilizer were added to a mixer and mixed at 180°C for 40 minutes, and then put into a mixing extruder for extrusion. The parameters were as follows: head temperature of 185°C, screw speed of 230 r / min, extrusion pressure of 12 MPa, and shear rate of 240 s-1 , pelletizing to obtain modified polypropylene particles;

[0038] (3) Place the modified polypropylene particles in a vacuum of 5.0x10 -3 Pa environment, then, argon gas was filled at a flow rate of 40sccm, and cleaning was carried out in sequence at a bias voltage of 300V and an ion beam voltage of 900V, each time for 10min, and mixed plasma was introduced by magnetron sputtering silicon target, tungsten target and yttrium target, and the plasma currents of silicon, tungsten and yttrium were controlled to 2.5A, 0.3A and 0.4A, respectively. Under the conditions of argon flow rate of 45sccm and bias voltage of -60V, deposition was carried out for 4 to 6h to obtain antistatic and antibacterial modified polypropylene particles.

[0039] Comparative Example 1

[0040] The difference between Comparative Example 1 and Example 2 is that step (1) is different. Step (1) is changed to: under nitrogen protection, 11 parts of allylhydrazine hydrochloride, 103 parts of toluene, and 62 parts of acetonitrile are mixed uniformly, the rotation speed is adjusted to 140 rpm, 3 parts of Phillips catalyst are added, propylene gas is introduced to 5 MPa, the temperature is raised to 65° C., and the reaction is carried out for 6 hours. During the reaction, propylene gas is continuously introduced to keep the pressure unchanged. After the reaction is completed, the air is connected, 22 parts of 3 mol / L hydrochloric acid ethanol solution is added, and the mixture is stirred for 50 minutes. The solid is filtered and washed with deionized water for 3 times, and dried at 80° C. for 8 hours to obtain modified polypropylene. The remaining steps are the same as those in Example 2.

[0041] Comparative Example 2: The difference between Comparative Example 2 and Example 2 is that step (1) is different. Step (1) is changed to: under nitrogen protection, 17 parts of ethylene potassium trifluoroborate, 103 parts of toluene, and 62 parts of acetonitrile are mixed evenly, the rotation speed is adjusted to 140rpm, 3 parts of Phillips catalyst are added, propylene gas is introduced to 5MPa, the temperature is raised to 65°C, and the reaction is carried out for 6h. During the reaction, propylene gas is continuously introduced to keep the pressure unchanged. After the reaction is completed, the air is connected, 22 parts of 3mol / L hydrochloric acid ethanol solution is added, and the mixture is stirred for 50min. The solid is filtered and washed with deionized water for 3 times, and dried at 80°C for 8h to obtain modified polypropylene. The remaining steps are the same as those in Example 2.

[0042] Comparative Example 3: The difference between Comparative Example 3 and Example 2 is that step (3) is different. Step (3) is changed to: placing the modified polypropylene particles in a vacuum of 5.0x10 -3Pa environment, then, argon gas was filled at a flow rate of 40sccm, and cleaning was carried out successively at a bias voltage of 300V and an ion beam voltage of 900V, each time for 10min, and mixed plasma was introduced by magnetron sputtering of tungsten target and yttrium target, and the tungsten and yttrium plasma currents were controlled to be 0.3A and 0.4A respectively, and the antistatic and antibacterial modified polypropylene particles were obtained under the conditions of argon gas flow rate of 45sccm and bias voltage of -60V. The remaining steps were the same as in Example 2.

[0043] Comparative Example 4: The difference between Comparative Example 4 and Example 2 is that step (3) is different. Step (3) is changed to: placing the modified polypropylene particles in a vacuum of 5.0x10 -3 Pa environment, then, argon gas was filled at a flow rate of 40sccm, and cleaning was performed successively at a bias voltage of 300V and an ion beam voltage of 900V, each time for 10min, and mixed plasma was introduced by magnetron sputtering silicon target and yttrium target, and the silicon and yttrium plasma currents were controlled to be 2.5A and 0.4A respectively, and the deposition was performed for 4 to 6h under the conditions of an argon gas flow rate of 45sccm and a bias voltage of -60V to obtain antistatic and antibacterial modified polypropylene particles. The remaining steps are the same as in Example 2.

[0044] Comparative Example 5: The difference between Comparative Example 5 and Example 2 is that step (3) is different. Step (3) is changed to: placing the modified polypropylene particles in a vacuum of 5.0x10 -3 Pa environment, then, argon gas was filled at a flow rate of 40sccm, and cleaning was carried out successively at a bias voltage of 300V and an ion beam voltage of 900V, each time for 10min, and mixed plasma was introduced by magnetron sputtering silicon target and tungsten target, and the silicon and tungsten plasma currents were controlled to be 2.5A and 0.3A respectively, and the deposition was carried out for 4 to 6h under the conditions of argon gas flow rate of 45sccm and bias voltage of -60V to obtain antistatic and antibacterial modified polypropylene particles. The remaining steps are the same as those in Example 2.

[0045] Comparative Example 6: The difference between Comparative Example 6 and Example 2 is that there is no step (3), and step (2) is changed to: 102 parts of modified polypropylene, 10 parts of silicon dioxide, 2 parts of tungsten dioxide, 2 parts of yttrium oxide, 5 parts of distearamide, 8 parts of antioxidant 1010, and 3 parts of benzotriazole light stabilizer are added to a mixer and mixed at 170°C for 35 minutes, and then put into a mixing extruder for extrusion. The parameters are: head temperature of 170°C, screw speed of 215r / min, extrusion pressure of 11MPa, shear rate of 230s -1 The remaining steps are the same as those in Example 2.

[0046] Effect example

[0047] Table 1 below shows the performance analysis results of the antistatic and antibacterial modified polypropylene particles of Examples 1 to 3 of the present invention and Comparative Examples 1 to 6.

[0048] Table 1

[0049]

[0050] From the comparison of the experimental data of Examples 1, 2, and 3 with Comparative Example 1, it can be found that the introduction of fluorine and boron elements through potassium ethylene trifluoroborate can penetrate the bacterial cell membrane, destroy the bacterial metabolic process, inhibit the growth and reproduction of bacteria, and achieve an antibacterial effect. At the same time, the presence of potassium ions can increase its conductivity and hygroscopicity by adsorbing water molecules in the air, thereby achieving an antistatic effect. From the comparison of the experimental data of Examples 1, 2, and 3 with Comparative Example 2, it can be found that the chloride ions in allyl hydrazine hydrochloride can inhibit the growth and reproduction of bacteria and enhance the antibacterial performance. At the same time, the hydrazide structure has a high reactivity, and the plasma current makes the amorphous silicon film more tightly bonded, further enhancing the mechanical strength. From the comparison of the experimental data of Examples 1, 2, and 3 with Comparative Example 3, it can be found that the in-situ growth of amorphous silicon film on the surface of polypropylene particles can significantly improve the mechanical strength of polypropylene and increase the wear resistance. From the comparison of the experimental data of Examples 1, 2, and 3 with Comparative Example 4, it can be found that the doping of tungsten elements , can reduce the friction coefficient of the amorphous silicon film, reduce wear when friction occurs, thereby improving the wear resistance of the plastic, enhancing the mechanical properties, and forming a conductive network on the surface, so that the generated static charge leaks quickly, achieving an antistatic effect; from the comparison of the experimental data of Examples 1, 2, and 3 with Comparative Example 5, it can be found that the yttrium element can fill the defects of polypropylene and the film grains, refine the grains, increase the grain boundary area, and enhance the barrier effect of the grain boundary on dislocations, thereby reducing the dislocation density of the material, improving the mechanical strength and flexibility of the material, and forming a conductive network on the surface, so that the generated static charge leaks quickly, achieving an antistatic effect; from the comparison of the experimental data of Examples 1, 2, and 3 with Comparative Example 6, it can be found that the CC bonds and CH bonds in the modified polypropylene particles are bombarded by plasma current to form active chains, which are combined with the mixed plasma, and the active chains react with each other to form a stable cross-linked structure, which prevents the active chains from continuing to overflow, and significantly improves the overall mechanical strength of polypropylene.

[0051] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.

Claims

1. A yellowing-resistant flame-retardant plastic and a preparation method thereof, characterized in that: The method comprises the following preparation steps: (1) Under nitrogen protection, 11-23 parts of potassium ethylene trifluoroborate, 5-17 parts of allylhydrazine hydrochloride, 74-132 parts of toluene, and 46-78 parts of acetonitrile are mixed uniformly, the rotation speed is adjusted to 140 rpm, 2-4 parts of catalyst are added, propylene gas is introduced to a certain pressure, the temperature is raised to 60-70° C., and the reaction is carried out for 4-8 hours. During the reaction, propylene gas is continuously introduced to keep the pressure constant. After the reaction is completed, the air is connected, 15-29 parts of hydrochloric acid ethanol solution are added, and the mixture is stirred for 40-60 minutes. The solid is filtered out, washed with deionized water for 3 times, and dried at 70-90° C. for 6-10 hours to obtain modified polypropylene; (2) adding 85 to 119 parts of modified polypropylene, 3 to 7 parts of lubricant, 5 to 11 parts of antioxidant, and 1 to 5 parts of benzotriazole light stabilizer into a mixer and mixing for 30 to 40 minutes, putting into a mixing extruder for extrusion, and pelletizing to obtain modified polypropylene pellets; (3) Place the modified polypropylene particles in a vacuum of 5.0x10 -3 Pa environment, then, filled with argon, and cleaned in sequence at a bias voltage of 300 V and an ion beam voltage of 900 V, each time for 10 min, introduced a mixed plasma by magnetron sputtering of silicon target, tungsten target and yttrium target, and controlled the plasma currents of silicon, tungsten and yttrium, and deposited for 4 to 6 hours under the conditions of an argon flow rate of 45 sccm and a bias voltage of -60 V to obtain antistatic and antibacterial modified polypropylene particles.

2. The yellowing-resistant flame-retardant plastic and the preparation method thereof according to claim 1, characterized in that: The certain pressure in step (1) is 5 MPa.

3. The yellowing-resistant flame-retardant plastic and the preparation method thereof according to claim 1, characterized in that: The catalyst in step (1) is any one of a Ziegler-Natta catalyst, a Phillips catalyst, and a Metallocene catalyst.

4. The yellowing-resistant flame-retardant plastic and the preparation method thereof according to claim 1, characterized in that: The concentration of hydrochloric acid in the hydrochloric acid ethanol solution in step (1) is 3 mol / L.

5. The yellowing-resistant flame-retardant plastic and the preparation method thereof according to claim 1, characterized in that: The lubricant in step (2) is any one of stearic acid acetamide, distearyl amide, and oxidized polyethylene wax.

6. The yellowing-resistant flame-retardant plastic and the preparation method thereof according to claim 1, characterized in that: The antioxidant in step (2) is any one of butylated hydroxytoluene, antioxidant 1010, and antioxidant 1076; the light stabilizer is.

7. The yellowing-resistant flame-retardant plastic and the preparation method thereof according to claim 1, characterized in that: The temperature of the mixer in step (2) is 160-180°C.

8. The yellowing-resistant flame-retardant plastic and the preparation method thereof according to claim 1, characterized in that: The parameters of the mixing extruder in step (2) are: head temperature 155-185°C, screw speed 200-230r / min, extrusion pressure 10-12MPa, shear rate 220-240s -1 .

9. The yellowing-resistant flame-retardant plastic and the preparation method thereof according to claim 1, characterized in that: The flow rate of argon gas in step (3) is 40 sccm.

10. The yellowing-resistant flame-retardant plastic and the preparation method thereof according to claim 1, characterized in that: In step (3), the silicon, tungsten and yttrium plasma currents are 2.5A, 0.3A and 0.4A respectively.

Citation Information

Patent Citations

  • PP nano composite material and preparation method thereof

    CN110229412A

  • Low-resistance antistatic functional non-woven fabric and production process thereof

    CN112376167A

  • Wear-resistant nano antibacterial polypropylene particle and preparation method thereof

    CN114479275A

  • NANO antibacterial and antifouling plastic particles for tables and chairs and preparation method

    WO2022021908A1